STATISTICAL STUDY ON THE ANTHROPOMETRIC PROFILE OF THE 5TH GRADE PUPILS - Mihai Ciubotaru (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
This study represents the anthropometric evaluation of the 5th grade students from Liceul Tehnologic "Iorgu Vârnav Liteanu", Liteni, Suceava. Anthropometric evaluation is a means of estimating physical development centered on measurements of the human body, on certain segments or on the whole body. The main aspect of anthropometric evaluation is the comparison of results from a mathematical point of view, through figures, graphs. The purpose of this experimental study on the anthropometric profile of the fifth grade student is to identify the results of the two measurements, initial and final, comparing them and recommending means of somato-functional development in physical education to discover an ideal shape of the human body.